Diagnostic performance of pre-procedure endoscopic biopsies in predicting the histology of gastric lesions undergoing ESD - Xu, Qin; Yang, Jinlei; Shi, Zhenwang; Fang, Dong; Bao, Deming; Wang, Liming (Frontiers in Oncology, 2025)
Gastric cancer remains one of the most lethal malignancies worldwide. Endoscopic submucosal dissection (ESD), a minimally invasive procedure that has become the gold standard for early-stage gastric cancer management, demonstrates both diagnostic and therapeutic utility. With advancing ESD techniques and expanded clinical applications, discrepancies between preoperative biopsy findings and post-resection pathology evaluations have become increasingly evident in clinical practice. This retrospective analysis of 113 ESD-treated patients employed systematic comparative methods to quantify diagnostic discrepancies between initial biopsy interpretations and definitive histopathological assessments, while identifying critical contributing factors. Multivariate analysis revealed three independent predictors of histopathological discrepancies including lesion location, lesions exhibiting type IIc morphology and elevated Kyoto Gastric Cancer Risk Scores. These findings provide robust statistical evidence for refining preoperative risk stratification protocols, ultimately optimizing clinical outcomes in precision endoscopy.